Primal leadership - Goleman, Daniel (Harvard Business Review Press, 2013)
Managers and professionals across the globe have embraced Primal Leadership, affirming the importance of emotionally intelligent leadership. Its influence has also reached well beyond the business world: the book and its ideas are now used routinely in universities, business and medical schools, and professional training programs, and by a growing legion of professional coaches